Cyclic behaviour of high strength friction grip bolt subjected to repeated tensile loading / Mohd Tajol Hasnan Ghazali - Ghazali, Mohd Tajol Hasnan (1997)
Fatigue is a common failure in Civil Structure that have not fully explored in researched, particularly for structures connected by bolts. Furthermore, there are many uncertainties in determining fatigue failure'as mention by many researchers regarding fatigue parameters. However, discerning from the researched pattern most of the study based on S-N Curve. This could well' mean that S-N Curve needs to be developed. The aims of this research are to propose a design monograph S-N Curve and to study the behavior of 12 mm diameter of Fligh Strength Friction Crip Bolt under repeated loading. The objectives of the studies were concentrated on the influence of Stress Ranges, Mean stress and the diameter of bolt with respect to the fatigue life. The methodology of research was a series of laboratory experiment. It started from Static Tensile Test, Fatigue Sensitivity Test and finally to conduct Fatigue Test on three levels of Mean Stresses at four different Stress Ranges. The finding from the experiment lay out in this paper were a proposal of the S-N Curve for 12 mm diameter HSFC Bolt and the effect of Stress Ranges and Mean Stresses to the bolts. The paper had discussed about a common point of endurance limit found in the experiment and the significant effect of Stress Range compared to the Mean Stress in fatigue life. The research had also determined under repeated loading that the smaller diameter of bolt can survive longer than bigger diameter. Finally, base on experiment conducted it is concluded that in fatigue design the pulsating tensile mode analysis is more critical than alternating mode.